Constructivist Approach in Ottoman Mathematics Education: Salih Zeki - Takıcak, Müjdat (Ninety Nine Publication, 2021)
In this study, it is aimed to determine whether the mathematics education approach of Salih Zeki, one of the late Ottoman mathematicians, has a constructivist character. For this purpose, 6 geometry textbooks written by Salih Zeki at middle school level were examined. Document analysis method was used in the research. In order to determine whether the textbooks have a constructivist character, 11 criteria have been determined and books have been analyzed based on these criteria. According to the results obtained, 6 geometry textbooks written by Salih Zeki have a constructivist character.
Keywords: 4. Education